Dribbling Training Methods 15 yard Turn and 20 yard Squared For Improving Results Undikma Football - Susi Yundarwati; Intan Primayanti (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2021)
The aim is to see the effect of the 15 yard turn and 20 yard squared dribbling training methods on the improvement of UNDIKMA football dribbling results, lacking in terms of agility, speed and balance, when dribbling. The design method used in this study is a design or design with an experimental model. This type of research uses the Experiment "Two Group Pretest-posttest Design. The sampling technique used purposive sampling where 22 UNDKMA players were divided into 2 groups. From the results of data analysis the effect of the dribbling training method 15 yard turn and 20 yard squared increase the results of UNDIKMA football dribbling. The value of tcount between 15 yard turn dribbling and X1 (dribbling) is tcount 7,358. The value of tcount between X2 is 20 yards squared (dribbling) of 7,358, and the value of tcount simultaneously between Y and X1, X2, draws from the table analysis at a significant level of 5% with a sample size of 11-1 = 10 of 1,812. that the hypothesis "Ha" (accepted), then this research is significant) Conclusion of the 15 yard turn and 20 yard squared dribbling training methods, the increase in the results of UNDIKMA football dribbling can improve football bling soccer. Keyword: dribbling 15 yard turn, 20 yard squared, dribbling Soccer